Stable and Surface‐active Co Nanoparticles Formed from Cation (x) Promoted Au/x‐Co3O4 (x=Cs) as Selective Catalyst for [2+2+1] Cyclization Reactions. Issue 5 (27th January 2021) - Oseghale, Charles O.; Mogudi, Batsile M.; Onisuru, Oluwatayo Racheal; Akinnawo, Christianah Aarinola; Fapojuwo, Dele Peter; Meijboom, Reinout
Abstract: Surface‐active and highly stable cobalt nanoparticles generated from alkali ion‐promoted gold catalyst for catalyzed carbonylative [2+2+1] cyclization reaction, is described. The gold nanoparticle's (AuNPs) role was assumed to dissociate the CO and H2 into atomic species on the catalyst surface by spillover, which in‐situ reduces the robust mesoporous cobalt oxide to metallic cobalt (Co 3+ →Co 2+ →Co), as the active catalytic species that catalyzed the reaction; thereby providing up to 93 % yield of cyclopentenone adducts. Prior to this, catalyst pre‐treatment with H2 gas (130 °C, 3 h, 20 atm) was performed to reduce the catalyst. It appeared that the low reducibility temperature and increased surface basicity ascribed to the presence of alkali ion‐promoters in the catalyst revealed a strong correlation with the catalyst activity, for the intra‐ and intermolecular reactions under milder reaction conditions. Thus, a sustainable, highly reusable, and environmentally friendly green catalyst for the carbonylation reaction, such as Pauson‐Khand, was developed. Abstract : Carbonylation reaction : Surface‐active and highly stable cobalt nanoparticles were generated on the catalyst surface. The gold nanoparticle's role was assumed to assist in the spillover of the H2 and CO gas, which in‐situ reduces Co3 O4 to metallic Co, as the active catalytic species that catalyzed the [2+2+1] cyclization reaction.